Epidemiological incidence and clinicopathological features of gastrointestinal perforation in tertiary care centre - Sandu, Sukhmandeep Singh; Kaur, Parneet (International Surgery Journal, 2025)
Background: Gastrointestinal (GI) perforations remain life-threatening surgical emergencies, particularly in developing countries. The present study aims to evaluate the incidence, clinical profile and histopathological characteristics of GI perforations and their association with morbidity and mortality. Methods: This prospective observational study included 64 patients diagnosed with gastrointestinal perforations and operated upon at a tertiary care institute in North India between August 2023 and February 2025. Clinical, intraoperative and histopathological data were recorded and analyzed. Results: The most commonly affected age group was 21-30 years (23.43%), with a male predominance (60.94%). Ileum was the most frequent perforation site (60.9%) followed by jejunum (17.2%) and duodenum (9.4%). The predominant causes of perforation were found to be infectious (typhoid and tuberculosis) accounting for 57.8%, followed by peptic ulcer (10.9%) predominantly with neoplasm/malignancy, obstructive pathologies, iatrogenic and ischemia being the other causes. Conclusions: GI perforations predominantly affect young males from lower socioeconomic strata and present most commonly in the ileum. Histopathology remains essential for etiological classification along with guiding both clinical management and preventive strategies. Early surgical intervention is key to reducing mortality.